Investment decision in human capital and macroeconomic implications - SANDU, Mihaela Tania; MIHAIL, Nora (Annals of Spiru Haret University. Economic Series, 2010)
To emphasize the importance and influence of human capital on economic growth of a country and also to base decisions on the need to invest in such type of capital, studies have been conducted and different models for analysis macroeconomic and demographic indicators have been used. We present the main indicators and dynamics of human capital, placed in the economic context of Romania, with reference, in bringing out statistics data, to an average period of time (between 1994-2008) characterized at macroeconomic level, both by recession and economic growth periods. There were also highlighted indicators and dynamics, both at national and individual level.